Psychometric comparisons of measures of eHealth literacy using a sample of Korean older adults. (1st February 2021) - Kim, Hyunjung; Yang, Eunjin; Ryu, Hyunju; Kim, Hee Jung; Jang, Sun Joo; Chang, Sun Ju
Abstract: Aims: This study aimed to compare the psychometric properties of two measures of eHealth literacy, namely, the Korean versions of the Digital Health Literacy Instrument (K‐DHLI) and eHealth Literacy Scale (K‐eHEALS), among older adults in South Korea. Background: Given the usefulness of eHealth information, measures of eHealth literacy have been developed. It is necessary to examine the validity of such tools among older adults who are likely to experience difficulties in using eHealth resources. Methods: A validation study was conducted using the secondary data of 180 older adults in South Korea. Two weeks after they had responded to the K‐DHLI and K‐eHEALS, 89 of them completed the assessments a second time so that the assessments' test–retest reliability could be examined. Using the collected data, their reliability (i.e. internal consistency, test–retest reliability) and validity (i.e. construct validity and criterion validity) were examined. Results: Both tools demonstrated satisfactory internal consistency (α ≥ 0.90, item‐total correlation coefficients = .39–.76) as well as good test–retest reliability with intraclass correlation coefficients .77 and .84, respectively. The 21 items of the K‐DHLI loaded onto five factors, which accounted for 71% of the variance. The 10 items of the K‐eHEALS loaded onto a single factor, which explained 58% of the total variance. The scores of both tools were strongly correlated ( r  = .63) and positively related to attitudes towards internet health information and subjective health status ( r  = .23–.50). Conclusions: The findings suggest that the K‐DHLI and K‐eHEALS are reliable and valid tools that can be used to assess the utilisation of eHealth resources by older adults. Implications for Practice: The findings can help healthcare providers choose a suitable measure of eHealth literacy when working with older adults.